Adaptation mechanisms of arsenic metabolism genes and their host microorganisms in soils with different arsenic contamination levels around abandoned gold tailings. (15th December 2021) - Li, Xianhong; Liu, Xiaoxia; Cao, Neng; Fang, Songjun; Yu, Caihong
Abstract: Soil around the gold tailing due to the smelting process of wastewater and solid waste can lead to metal (loids) contamination, especially arsenic (As). Soil microorganisms have gradually evolved adaptive mechanisms in the process of long-term adaptation to As contamination. However, comprehensive investigations on As metabolism genes and their host microbial communities in soil profiles with different levels under long-term As contamination are lacking. There are selected three typical soil profiles (0–100 cm) with different metal (loids) contamination levels (L-low, M-moderate and H-high) around tailings in this research. It uses a Metagenomic approach to explore the adaptation mechanisms of arsenic metabolism genes and arsenic metabolism gene host microorganisms in both horizontal and vertical dimensions. The results showed that four categories of As metabolism genes were prevalent in soil profiles at different As contamination, with As reduction genes being the most abundant, followed by As oxidation genes, then respiration genes and methylation genes. The As metabolism genes arsBCR, aioE, arsPH, arrAB increased with the increase of metal (loid) contaminants concentration. Longitudinal arsA, arrA, aioA, arsM and acr3 increased in abundance in deep soil. Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi were the dominant phylum of As metabolism gene host microorganisms. Different concentrations of metal (loid) contamination significantly affected the distribution of host As metabolism genes. Random forest prediction identified As as the most critical driver of As metabolism genes and their host microorganisms. Overall, this study provides a reference for a comprehensive investigation of the detoxification mechanisms of As metabolism microorganisms in soil profiles with different As contamination conditions, and is important for the development of As metabolism gene host microbial strains and engineering applications of microbial technologies to manage As contamination. Graphical abstract: Image 1 Highlights: We studied arsenic metabolism genes and host microbe around gold tailing soil. Arsenic reduction genes dominated the arsenic metabolism genes in gold tailing soils. Actinobacteria and Proteobacteria were the most abundant arsenic metabolism hosts. The total arsenic was the main driver of soil arsenic metabolism genes and the host. The arsBCDR, aioX, and arsH were significantly correlated with arsenic contents.